ESTUDIO PALINOLÓGICO DE LA FORMACIÓN BAQUERÓ (CRETACICO), PROVINCIA DE SANTA CRUZ. II (Ameghiniana, 2013)
In the present paper, second contribution to the palynology of the Baqueró Formation in Santa Cruz Province, six spores of the Cingulati group are described. A new genus, Heliosporites, with a single species H. baculatus is proposed for spores having radialIy striated cingulum, smooth proximal sculptures and distal strong baculas, spines 01' verrucae, Three other species known from Australia and U.S.A. are combined to this genus. The folIowing are new species: Polypodiaceoisporites elegans, Camarazonosporites microalceolatus and Muricingulisporis annulatus. Two konwn specíes- are recorded for the first time in Argentina: Foraminisporis dailyi (Cookson and Dettmann ) Dettmann, and Contignisporites cooksonii (Balme) Dettmann.